Slovakia: The Path From Monetary Sovereign to Common European Rules - Štrkolec, Miroslav (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter focuses on the monetary policy of Slovakia, a member of both the EU and the Eurozone. Slovakia’s membership in the euro area has fundamentally influenced, and continues to influence, its monetary policy. From the Slovak perspective, we distinguish between the period up to 2009, when the Slovak Republic – represented by the National Bank of Slovakia (NBS) – was the monetary sovereign, and the period from 2009 onwards, when the NBS participated in the common monetary policy set by the European Central Bank for the entire Eurozone. In the introduction, we highlight the historical background of Slovakia’s entry into the euro area in terms of its fulfilment of the convergence criteria. We also discuss the advantages and disadvantages of Eurozone membership in terms of assumptions and subsequent realities. The bulk of this chapter deals with the European Banking Union from the perspective of Slovakia, which, as a member of the Eurozone, is obliged to participate in its existing pillars. It takes a closer look at the powers entrusted to the national authorities (NBS, Resolution Board, Deposit Guarantee Fund) to achieve the objectives for which the banking union was created. Finally, the chapter concludes by highlighting Slovakia’s limited influence on the European Union’s monetary policy, in which it participates mainly through the NBS governor in the Governing Council of the European Central Bank.Keywords: monetary policy, convergence criteria, banking union, crisis resolution, deposit guarantee